EUROPEC/EAGE Conference and Exhibition 2009
DOI: 10.2118/121256-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Monte Carlo Simulation in Calculating HC-Reserves

Abstract: One of the key features of E&P companies is their proved reserves in hydrocarbon deposits. Reserve estimation requires knowledge of Initial Hydrocarbon in Place, technical reserves and economic conditions including annual cash flow estimation in the forecast period. Since all parameters used in evaluation procedure are burdened by rather more than less certainty. Therefore, in a sophisticated evaluation process, there should be determined not the expected values only (deterministic way), but errors/uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Zhang and Srinivasan in 2003 presented a methodology for generating MCMC (Markov Chain Monte Carlo) model of a geological system and described it in mathematical expressions (Zhang and Srinivasan, 2003). In 2009 Z. Komlosi and J. Komlosi used Monte Carlo simulation to estimate the amount of reserves in three oil fields (one anticline-type and the other two lithologic-type) and concluded that "Monte Carlo simulation's accuracy is determined by the reliability of the geo-technical model, parameters and conditions forecasted" (Komlosi and Komlosi, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Srinivasan in 2003 presented a methodology for generating MCMC (Markov Chain Monte Carlo) model of a geological system and described it in mathematical expressions (Zhang and Srinivasan, 2003). In 2009 Z. Komlosi and J. Komlosi used Monte Carlo simulation to estimate the amount of reserves in three oil fields (one anticline-type and the other two lithologic-type) and concluded that "Monte Carlo simulation's accuracy is determined by the reliability of the geo-technical model, parameters and conditions forecasted" (Komlosi and Komlosi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 Z. Komlosi and J. Komlosi used Monte Carlo simulation to estimate the amount of reserves in three oil fields (one anticline-type and the other two lithologic-type) and concluded that "Monte Carlo simulation's accuracy is determined by the reliability of the geo-technical model, parameters and conditions forecasted" (Komlosi and Komlosi, 2009).…”
Section: Introductionmentioning
confidence: 99%